First record of Lutzomyia (Lutzomyia) longipalpis (Diptera: Psychodidae: Phlebotominae) on the trinational frontier (Brazil-Peru-Bolivia) of South-Western Amazonia - Borges, Diones Antonio; Molina, Silvia Maria Guerra; Pinto, Mara Cristina [UNESP]; Galati, Eunice Aparecida Bianchi [UNESP]; Cesario, Manuel; Ortiz, Dennys Ghenry Samillan (Oxford University Press (OUP), 2017)
In South America, the main sand fly species involved in the transmission of Leishmania infantum chagasi (Cunha & Chagas, 1937), etiological agent of the visceral leishmaniasis (VL), is Lutzomyia longipalpis (Lutz & Neiva, 1912). The species has been recorded in Colombia, Venezuela, Bolivia, Argentina, Paraguay, Uruguay, and Brazil, where it is recorded in 24 of the 27 Brazilian states, except Acre, Amazonas, and Santa Catarina. Collections were carried out for one year (April 2013 to March 2014) using modified CDC light traps in different environments in Assis Brasil municipality, state of Acre. Two males of Lu. longipalpis were found in peridomiciliary location in a periurban area. This is the first record of the species in Acre. This finding may be considered by the health agencies located in the trinational frontier, and new collections are needed to evaluate the real distribution of the species.
Keywords: Acre; Monitoring; Sand fly; Spacial distribution; Visceral leishmaniasis